Apomorphine-induced yawning in rats is abolished by bilateral 6-hydroxydopamine lesions of the substantia nigra. - Stoessl, A; Dourish, C; Iversen, S (1987)
Apomorphine-induced yawning was studied in male rats with bilateral 6-hydroxydopamine lesions of the substantia nigra. Apomorphine 10, 20 and 50 micrograms/kg SC induced dose-dependent yawning in unoperated controls and animals with sham lesions. In the lesioned animals (in which the mean striatal dopamine depletion was 67%), the maximum yawning response rate was greatly attenuated with no evidence that the dose response curve was shifted in either direction. Furthermore, blockade of yawning in the lesioned animals was not simply due to suppression by other stereotyped behaviours, since there was no evidence of increased sniffing or chewing in these animals. These data provide further support for the hypothesis that apomorphine-induced yawning is mediated by dopamine autoreceptors and requires intact nigrostriatal projections.